Comparative analysis for producing sweetpotato pre-basic seed using sandponics and conventional systems - Makokha, P.; Ssali, R.T.; Rajendran, S.; Wanjala, Bramwel W.; Matasyoh, L.G.; Kiplagat, O.K.; Low, Jan W.; McEwan, M. (Informa UK Limited, 2020)
In Sub-Saharan Africa, sweetpotato pre-basic seed is multiplied in screenhouses using a sterilized soil substrate. This is expensive and unsustainable. The use of sand substrate with a fertigation system (“sandponics”), is an alternative. The study compared the cost-effectiveness for pre-basic seed production using the sandponics system to the conventional soil substrate for four genotypes. A randomized complete block split plot design was used, and data collected on vine traits over six harvests. Real-time cost data were collected for cost-effectiveness analysis. Results showed a highly significant (p < .0001) 21.8% increase in the vine multiplication rate under the sandponics system. The cost of producing one sweetpotato node in sandponics was significantly lower by 0.009 US$. The cost-effectiveness of producing pre-basic seed in sandponics varied among the genotypes. The future use of sandponics is discussed with respect to the availability of soluble inorganic fertilizers, varietal specific response to nutrients, and labor implications.